Gain Flattening and Noise Figure Analysis of EDFA WDM Configuration for L-band Optical Communication using Wavelength Selective Attenuator - Pain, Somnath; Biswas, Mousumi; Biswas, Sambhunath (Photonics Letters of Poland, 2013)
In Erbium Doped Fiber Amplifier, there are basically two main techniques for gain flattening: one is use external wavelength filters to flattenedthe gain while the other one relies on modifying the amplifying fiber properties to flattened the gain spectrum. The paper presents the study of simulation of a gain flattened EDFA WDM network for L-band optical communication using Wavelength Selective Attenuator .The design provides a high gain of 34.63dB at 1593nm and gain flatness (P-P) 0.38dB by using wavelength selective attenuator in the entire L-band at room temperature. Noise figure of less than 11dB was found in the entire 37nm (1571nm-1608nm) region very promisingly. The variation also been studied for various values of fiber lengths and pump powers. Full Text: PDF References M.Yamada, H.ono, T.Kananori, S.Sudo and Y.Ohishi, "Broadband and gain-flattened amplifier composed of a 1.55 ?m-band and a 1.58 ?m-band Er3+-doped fibre amplifier in a parallel configuration", Electron Lett., 33, 8 (1997). CrossRef Y.Sun, J.W.Sulhoff, A.K.Srivastava, J.L.Zyskind, T.A.Strasser, J.R.Pedrazzani, C.Wolf, J.Zhou, J.B.Judkins, R.P.Espindola, A.M.Vengsarkar, "Performance of coherent receiver with weighted despreading sequence for DS-CDMA", Electron Lett.33,23(1997) CrossRef Caugale Sachin et al, 2nd International Conference on Machanical ans electronics Engineering (ICMEE 2010) Goel Aditya et al, "Design of broadband EDFA for next generation optical networks", Journal of neural networks and application, pp.9-13 jan ? june 2011. L.L.Yi, L.Zhan, J.H.Ji,Q.H. Ye and Y.X.Xia, "Improvement of gain and noise figure in double-pass L-band EDFA by incorporating a fiber Bragg grating", IEEE Photonics Technology Letters,16,4,(2004). CrossRef M.Yamada, A.Mori, K.Kobasyashi, H.Ono, T.Kanamori, K.Oikawa, Y.Nishida and Y.Ohishi, "Gain-flattened tellurite-based EDFA with a flat amplification bandwidth of 76 nm", IEEE Photon.Technology Lett. 10, 9 (1998). CrossRef T.K.Bandhopadhya, Manish Saxena, Akash Tiwari, "Jitter?s Alpha Stable Distribution Behavior", International journal of Computer Technology and Electronics Engineering, 3,1,(2013). DirectLink M.Pal, M Paul, S.Bandyopadhyay, P.Biswas, K.Dasgupta and S.Bhadra, Fiber Optics Laboratory. CGCRI, Kolkata, India. 2012 Liu Kaixian, Du Juan, "Research of EDFA gain flattening based on chirped fiber Bragg grating", Proceeding of IC-BNMT 2009. CrossRef E. Desurvire, "Erbium Doped Fiber Amplifiers: Principles and Applications", New York: Wiley, 1994, pp. 268?270. K.Thyagarajan, A.Ghatak, "Fiber Optic Essentials", IEEE Press,John Wiley &Sons,Inc.2007